Effects of Music in supermarket : Employee's reaction - Chuo, Heidi Sin Ai (Universiti Malaysia Sarawak (UNIMAS), 2012)
This research focused on the supermarket employee's reaction of moods and behavior towards the music played in their workplace. The intention of this research was to examine the relationship of background music and employee's reaction, whether respondents like or dislike when the music being Player Questionnajres were distributed to eight supermarkets in Sibu town and total respondents obtained were 199. Collected data was analyzed by applying frequency analysis and factor analysis. The research found that respondent's mood and behavior are closely related to the music played in their working environment.